Potensi produk komersial berbahan aktif Beauveria bassiana sebagai agensia pengendalian Oryctes rhinoceros - Ardika, Made; Fitriana, Yuyun; Suharjo, Radix; Purnomo, Purnomo (Universitas Lampung, 2024)
The rhinoceros beetle, Oryctes rhinoceros, is a major pest on coconut and oil palm plants, attacking both in replanting areas and directly in farmers' fields. The O. rhinoceros beetle (Coleoptera: Scarabaeidae) holds the most important position as a pest of coconut plants, both in terms of its damaging ability, distribution, population stability, and year-round population size, and is widely recognized by coconut farmers. The use of microorganisms as biological agents is part of biological control efforts. One biological agent widely used as a bioinsecticide and proven to be quite effective is the entomopathogenic fungi group, such as Beauveria bassiana. The objectives of this research are as follows: 1). To determine the ability of a commercial product containing B. bassiana as an active ingredient to cause mortality in O. rhinoceros larvae; 2) To identify the effective dose that can cause high mortality in O. rhinoceros. This study used a Completely Randomized Design (CRD) with five treatments tested, namely: P1: 37.5 g B. bassiana; P2: 28.13 g B. bassiana; P3: 18.75 g B. bassiana; P4: 9.38 g B. bassiana; P5: control. Each treatment was repeated five times, and each replicate consisted of five samples, resulting in 25 experimental samples or a total of 125 O. rhinoceros larvae. Further analysis was conducted using the LSD test at a 5% significance level. Based on the research results, the commercial product containing B. bassiana as an active ingredient was able to cause mortality in O. rhinoceros. The most effective dose for controlling O. rhinoceros larvae was treatment 3, with a dose of 18.75 g, yielding an average mortality rate of 72%.